2016
DOI: 10.1186/s13052-016-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

Atopy and autoimmune thyroid diseases: melatonin can be useful?

Abstract: Recently, there has been growing interest in the relationship between allergic and autoimmune diseases. Allergy and autoimmunity can be considered two potential outcomes of dysregulated immunity and analysis of literature data shows a strong positive association between a history of Th2-mediated allergic disorders and Th1-mediated autoimmune disorders.Autoimmune thyroid diseases are the most common of all autoimmune pathological conditions.Currently, the mechanisms explaining an association among atopy, autoim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…It also has therapeutic potential for respiratory, colonic, autoimmune, adult-onset chronic non-communicable diseases, ischemic brain and cardiovascular injury, circadian disturbance, stroke, steatohepatitis, etc. [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Melatonin can efficiently scavenge a variety of ROS including hydrogen peroxide (H 2 O 2 ), hydroxyl radical (HO•), nitric oxide (NO•), singlet oxygen ( 1 O 2 ) and superoxide anion (O 2– •) [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also has therapeutic potential for respiratory, colonic, autoimmune, adult-onset chronic non-communicable diseases, ischemic brain and cardiovascular injury, circadian disturbance, stroke, steatohepatitis, etc. [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Melatonin can efficiently scavenge a variety of ROS including hydrogen peroxide (H 2 O 2 ), hydroxyl radical (HO•), nitric oxide (NO•), singlet oxygen ( 1 O 2 ) and superoxide anion (O 2– •) [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atopy refers to a tendency to produce IgE antibodies in response to low doses of allergens and presents with typical allergic symptoms [14]. Albeit the evidence linking atopy to autoimmune disorders is still controversial, several lymphocyte subsets (Th17, regulatory T cells) and IL-9 have been proposed as a common link [15]. One study in children suggested that atopy might overlap with thyroid autoimmunity as both resulted from dysregulated immunity [16].…”
Section: Discussionmentioning
confidence: 99%
“…Evolving evidence of interactions between thyroid hormone and basal mechanisms controlling appetite and energy expenditure, as well as between the regulation of insulin sensitivity and secretion, explains the possible association between AITD and metabolic diseases 21. Previous studies reported a higher incidence of AITD in patients with allergic disease, and the relationship between allergic and autoimmune diseases was elucidated as 2 potential outcomes of dysregulated immunity 222324…”
Section: Discussionmentioning
confidence: 99%
“… 21 Previous studies reported a higher incidence of AITD in patients with allergic disease, and the relationship between allergic and autoimmune diseases was elucidated as 2 potential outcomes of dysregulated immunity. 22 23 24 …”
Section: Discussionmentioning
confidence: 99%